Seesaw como herramienta virtual en la Enseñanza-Aprendizaje de Biología de los Microorganismos con los estudiantes de quinto semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Trujillo Averos, Maria Jose (2025)
This research proposes the implementation of the Seesaw virtual tool to improve the teaching and learning process in the subject of Biology of Microorganisms to fifth- semester students of the Experimental Sciences Pedagogy program (Chemistry and Biology) at Universidad Nacional de Chimborazo. The thesis is based on the framework of Learning and Knowledge Technologies (LKT), seeking to move beyond the instrumental use of ICTs toward a more strategic pedagogical application. The problem addressed in this research lies in the limited use of integrated technological tools, such as the Seesaw virtual platform. The methodology employed was quantitative, with a non- experimental, cross-sectional, and descriptive design. Data collection consisted of a survey administered to the entire study population of 29 students. The instrument was a questionnaire of 10 closed-ended questions created with Google Forms. The results obtained showed that the Seesaw tool is viable due to its high acceptance and perceived effectiveness, as it allows the integration of innovative teaching resources such as graphic organizers, interactive games, digital worksheets, and continuous feedback activities for the Mycology and Parasitology units. Since the tool significantly enhances the teaching and learning process through the "Paramycelium" digital portfolio, following the PACIE methodology, it has fostered a collaborative environment that promotes interactive, self- regulated, explanatory, participatory, independent, and cooperative learning, thus enriching the teaching and learning process